2021
DOI: 10.1038/s41467-021-24210-9
|View full text |Cite
|
Sign up to set email alerts
|

Shallow slow earthquakes to decipher future catastrophic earthquakes in the Guerrero seismic gap

Abstract: The Guerrero seismic gap is presumed to be a major source of seismic and tsunami hazard along the Mexican subduction zone. Until recently, there were limited observations at the shallow portion of the plate interface offshore Guerrero, so we deployed instruments there to better characterize the extent of the seismogenic zone. Here we report the discovery of episodic shallow tremors and potential slow slip events in Guerrero offshore. Their distribution, together with that of repeating earthquakes, seismicity, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…At shallow plate boundaries, VLFEs have been reported in landbased observations (e.g., Obara and Ito 2005). In recent years, seafloor observations have also been conducted and cable-based seafloor monitoring systems have been constructed, thereby enabling the observation of shallow slow earthquakes (Annoura et al 2017;Araki et al 2017;Ito et al 2015;Nishikawa et al 2019;Obana and Kodaira 2009;Ohta et al 2019;Plata-Martinez et al 2021;Tanaka et al 2019;Todd et al 2018;Tonegawa et al 2020;Wallace et al 2016;Yamashita et al 2015). Yamashita et al (2015) investigated the detailed properties of shallow low-frequency tremors (shallow tremors) in the Hyuga-nada region at the western end of the Nankai Trough, Japan, using ocean bottom observations of seismicity near the trench (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…At shallow plate boundaries, VLFEs have been reported in landbased observations (e.g., Obara and Ito 2005). In recent years, seafloor observations have also been conducted and cable-based seafloor monitoring systems have been constructed, thereby enabling the observation of shallow slow earthquakes (Annoura et al 2017;Araki et al 2017;Ito et al 2015;Nishikawa et al 2019;Obana and Kodaira 2009;Ohta et al 2019;Plata-Martinez et al 2021;Tanaka et al 2019;Todd et al 2018;Tonegawa et al 2020;Wallace et al 2016;Yamashita et al 2015). Yamashita et al (2015) investigated the detailed properties of shallow low-frequency tremors (shallow tremors) in the Hyuga-nada region at the western end of the Nankai Trough, Japan, using ocean bottom observations of seismicity near the trench (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main rupture characteristics of this earthquake shows that the rupture located upon 30 km contour are consistent with each other. Deep slow slip events are observed in the Oaxaca region and represent transient behaviors where the fault releases accumulated stress (Graham et al, 2016;Almeida et al, 2018;Cruz-Atienza et al, 2021). These slow slip events may release most down-dip shear stress, limiting the rupture area and hindering the coseismic down-dip rupture within this earthquake.…”
Section: Rupture Characteristicsmentioning
confidence: 99%
“…The creeping released the most stress and little stress, which would accumulate that nucleated small earthquake events in the shallowest part over the period between large earthquakes. Additionally, few slow slip events have been found on the shallow part of this fault (Cruz-Atienza et al, 2021;Plata-Martinez et al, 2021); this may be one of the reasons for the absence of the slip in the up-dip zone (Correa-Mora et al, 2009;Graham et al, 2014Graham et al, , 2016Obara and Kato, 2016;Maury et al, 2018;Cruz-Atienza et al, 2021). We calculated Coulomb failure stress change (Toda et al, 2005) using our rupture model, and the friction coefficient is set to 0.6 because previous studies have shown that thrust faults have high friction coefficients of around 0.8 (Freed et al, 2007;Xiong et al, 2010;Guo et al, 2020).…”
Section: Rupture Characteristicsmentioning
confidence: 99%
“…In addition, tectonic tremor has been observed most energetically in Oaxaca and Guerrero ( Cruz-Atienza et al, 2015, 2018A. L. Husker et al, 2012;Kostoglodov et al, 2010;Payero et al, 2008;Rivet et al, 2014;, and near the trench ( Plata-Martínez et al, 2021 ). Tremors form an almost continuous belt that extends from the state of Colima in the West through Oaxaca in the East, where very low frequency earthquakes appear during tremor activity ( Maury et al, 2016( Maury et al, , 2018.…”
mentioning
confidence: 99%
“…Tremors form an almost continuous belt that extends from the state of Colima in the West through Oaxaca in the East, where very low frequency earthquakes appear during tremor activity ( Maury et al, 2016( Maury et al, , 2018. This variety of mechanisms has led to several hypotheses about the seismic budget distribution ( Gualandi et al, 2017;Radiguet et al, 2012;Ramírez-Herrera et al, 2018 ) that suggest that a significant portion of the stress is released through aseismic slip in the seismic gap including its offshore segment ( Plata-Martínez et al, 2021 ). If these hypotheses held true, the GG would not likely have yet the potential to nucleate large megathrust earthquakes by itself.…”
mentioning
confidence: 99%